Analisis Sistem Pembiayaan Murabahah pada PT. BPRS Al Washliyah Medan - Aninditha Azka Safanah; Muhammad Lathief Ilhamy Nasution (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research was carried out at PT. BPRS Washliyah Medan. The aim of this research is to understand the murabahah financing system and process implemented by PT. BPRS Al-Washliyah Medan. Murabahah financing is a sale and purchase agreement for goods stating the acquisition price and profit agreed upon by the seller whose role in this case is the Bank and the buyer whose role is the customer/prospective customer for the customer's needs, with the flavone given Rp. 25,000,000 to Rp. 250,000,000. The principles of Murabahah financing are based on Islamic sharia and established legal provisions. Murabahah financing has apparently received a lot of responses from the public and business entities, but not many people and business entities understand the procedures for obtaining murabahah financing, even though marketing has been carried out by PT. SRB Washliya.